EVALUATION OF THE QUALITY OF ACADEMIC ADMINISTRATION SERVICESAT THE FACULTY OF VOCATIONAL SCIENCES, UNIVERSITY OF NORTH SUMATRA - Akbar Reza Pratama; Meilita Tryana Sembiring; Evawany Yunita Aritonang (International Journal of Economic, Business, Accounting, Agriculture Management and Sharia Administration (IJEBAS), 2025)
Academic administration services are a crucial component in supporting the smooth running of higher education, particularly within the Faculty of Vocational Studies, which emphasizes speed, accuracy, and efficiency. This study aims to evaluate the quality of academic administration services at the Faculty of Vocational Studies, University of North Sumatra, based on student perceptions, identify barriers in the service process, and explore user expectations and input on service quality improvements. The approach used was descriptive qualitative, with data collection techniques through in-depth interviews, observation, and documentation of 10 purposively selected respondents. The results showed that service quality was considered quite good in terms of reliability and tangibles, but weaknesses remained in the dimensions of responsiveness, empathy, and assurance. Obstacles found included: lack of clarity in procedural information, unresponsiveness from staff, the absence of an online document tracking system, and minimal empathy in service communications. Service users expect improvements in interpersonal communication, procedural consistency, and accelerated service through the digitization of the administrative system. Therefore, improving the quality of academic administration services needs to focus on strengthening staff competencies, developing technology-based service systems, and establishing a humanistic and responsive service culture.